Immigration and the Diffusion of Technology: The Huguenot Diaspora in Prussia - Erik Hornung (Verein für Socialpolitik, 2010)
This paper analyzes the long-term effect of technological diffusion on productivity caused by immigration of skilled workers. In 1685 religious persecution drove highly skilled Huguenots into the backward Brandenburg-Prussia where they established themselves and transferred technological knowledge to natives. We find that textile manufactories installed in towns hosting the Huguenots achieved higher productivity than others due to diffusion, even 100 years after immigration. Identification is based on an instrumental variable approach exploiting variation in the settlement of Huguenots which results from population losses due to plagues during the Thirty Years' War, effectively eliminating worries of selectivity in the settlement pattern.
Keywords: N33; O15; O33; 330; Migration; Technological Diffusion; Human capital; Huguenots; Prussian economic history